Identification of Soluble Mediators in IgG-Mediated Anaphylaxis via Fcγ Receptor: A Meta-Analysis - Kow, Audrey Siew Foong; Chik, Azirah; Soo, Kuan-Meng; Khoo, Leng Wei; Abas, Faridah; Tham, Chau Ling (Frontiers in Immunology, 2019)
Background Anaphylaxis is an acute and possibly life-threatening allergic response. Classically and most commonly, it can be mediated by the crosslinking of allergens to immunoglobulin (Ig) E- high affinity IgE receptor (FcεRI) complex found mostly on mast cells. However, there is another pathway of anaphylaxis that is less well studied. This pathway known as the alternative pathway is mediated by IgG and its Fc gamma receptor (Fcγ). Though it was not documented in human anaphylaxis, a few studies have found that IgG-mediated anaphylaxis can happen as demonstrated in murine model of anaphylaxis. In these studies, a variety of biomarkers were being evaluated and they differ from each study which causes confusion in the suitability and reliability of choice of biomarkers to be analysed for diagnosis or therapeutic purposes. Hence, the objective of this meta-analysis is to identify the key potential biomarkers that are involved in an IgG-mediated anaphylaxis reaction. Methods Studies related to IgG-mediated anaphylaxis were sourced from three search engines namely PubMed, Scopus and Ovid from 1994 to 2018. Relevant studies were then reviewed based on specific inclusion factors. The levels of each biomarker studied were then extracted by means of ImageJ or Get Data Graph Digitiser software and the data were subjected to meta-analysis. Results From our findings, we found that histamine, serotonin, platelet activating factor (PAF), β-hexosaminidase, leukotriene C4 (LTC4), mucosal mast cell protease-1 (MMCP-1), interleukins (IL)-4, -6, and -13; tumour necrosis factor alpha (TNF-α) and macrophage inflammatory protein-1α (MIP-1α) were often being analysed. Out of these biomarkers, histamine, PAF, β-hexosaminidase, IL-6 and -13, MIP-1α and TNF-α were more significant with positive effect size and p-value of less than 0.001. As study effect was relatively small, we performed publication bias and found that there was publication bias and this could be due to the small sample size studied. Conclusion As such, we conclude that through meta-analysis, the key potential biomarkers involved in IgG-mediated anaphylaxis to be histamine, PAF, β-hexosaminidase, IL-6 and -13 and MIP-1α and TNF-α but will require further studies with larger sample size.